Nanooncology Engineering nanomaterials for cancer therapy and diagnosis (Nanomedicine and Nanotoxicology, 2018)
This book presents a systematic overview of the most relevant nanomaterials and their respective intrinsic properties that have been highly explored by the scientific community and pharmaceutical companies in several different modalities for cancer therapy and bioimaging. The chapters explore the synergistic effects provided by the different nanostructured materials and highlight the main in vitro and in vivo therapeutic achievements on cancer. This work also provides relevant discussion about the recent progresses and future challenges that nanotechnology faces on the conception of more efficient nanoformulations against primary tumors, circulating cancer cells and metastases.